2016
DOI: 10.1063/1.4942018
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between photoexcited NIR emitting CdHgTe quantum dots and graphene oxide

Abstract: Hydrothermally grown mercury cadmium telluride quantum dots (CdHgTe QDs) are decorated on graphene oxide (GO) sheets through physisorption. The structural change of GO through partial reduction of oxygen functional groups is observed with X-ray photoelectron spectroscopy in GO-QDs composites. Raman spectroscopy provides relatively a small change (∼1.1 times) in D/G ratio of band intensity and red shift in G band from 1606 cm−1 to 1594 cm−1 in GO-CdHgTe QDs (2.6 nm) composites, which indicates structural modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…To reach the SWIR range with HgTe , smaller nanocrystals (i.e., with more confinement) than the one used for MWIR have to be grown. Alternatively a ternary alloy with Cd , can be synthetized. However, in the latter case very small Cd content needs to be introduced which generates difficulties to finely reproduce the band gap from batch to batch.…”
Section: Introductionmentioning
confidence: 99%
“…To reach the SWIR range with HgTe , smaller nanocrystals (i.e., with more confinement) than the one used for MWIR have to be grown. Alternatively a ternary alloy with Cd , can be synthetized. However, in the latter case very small Cd content needs to be introduced which generates difficulties to finely reproduce the band gap from batch to batch.…”
Section: Introductionmentioning
confidence: 99%
“…After the CQD layer dried, a graphene oxide (GO) layer was dispersed over it to form a top contact that was transparent to MWIR. In previous studies, we showed that GO is an excellent system for electron extraction from photoexcited, NIR-emitting Hg0.2Cd0.8Te CQDs [29]. Implementation of a top contact using ITO resulted in poor transparency in MWIR spectral range.…”
Section: Fpa Development and Experimentalmentioning
confidence: 98%
“…Among the solution‐based formation processes, hydrothermal (HT) and ST methods are also popular and have been extensively used in the synthesis of various semiconductor solid‐solution nanostructures due to their facile operation and simple setup . Typically, the synthesis is conducted in a sealed autoclave at elevated temperature and pressure or in three‐neck flask under Ar flux protection . Under such experimental conditions, water and nonaqueous solvents display different properties such as viscosity and dissociation constant which can promote the mass transportation, the control of nucleation, and the growth rate, as well as morphology during the growth process of nanomaterials .…”
Section: Synthetic Strategies Of Semiconductor Solid‐solutionsmentioning
confidence: 99%
“…In addition to the above synthesis methods for obtaining semiconductor solid‐solution nanostructures, the synthetic technologies including sol‐gel method, electrospinning (ES) methods, reflux, TP methods, and microwave irradiation have also been reported. However, it should be noted that some modified reaction strategy combining with different processes is often utilized for a controllable synthesis route of semiconductor solid‐solution nanostructures.…”
Section: Synthetic Strategies Of Semiconductor Solid‐solutionsmentioning
confidence: 99%